2023
DOI: 10.1002/pssa.202200689
|View full text |Cite
|
Sign up to set email alerts
|

Optical, Optoelectronic, and Third‐Order Nonlinear Photonics of Ultrathin Molybdenum Oxide Film Deposited by Atomic Layer Deposition

Abstract: The atomic layer deposition (ALD) technique has attracted significant attention because it enables the control of film synthesis at the subnanometre scale. Herein, molybdenum oxide (MoO3) ultrathin films using the ALD system through Bis(t‐butylimido)bis(dimethylamino)molybdenum (VI) as a molybdenum (Mo) source are prepared. To understand the effect of deposition temperature, thin films are prepared at three different temperatures 100, 150, and 250 °C. The morphological and elemental properties are assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The preparation of a MoO 3 thin film using ALD (AT410 ALD system—ANRIC Technologies, Billerica, MA, USA) was described previously [ 28 ]. Briefly, the samples were deposited with Ozone source (ATO 3 ozone system—ANRIC Technology, Toronto, ON, Canada) as an oxidizing source and bis(t-butylimido)bis(dimethylamino)molybdenum (VI) as the molybdenum (Strem Chemicals, Newburyport, MA, USA) source [ 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of a MoO 3 thin film using ALD (AT410 ALD system—ANRIC Technologies, Billerica, MA, USA) was described previously [ 28 ]. Briefly, the samples were deposited with Ozone source (ATO 3 ozone system—ANRIC Technology, Toronto, ON, Canada) as an oxidizing source and bis(t-butylimido)bis(dimethylamino)molybdenum (VI) as the molybdenum (Strem Chemicals, Newburyport, MA, USA) source [ 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the film thickness increased with an increasing deposition temperature. According to the authors, the films that were grown at a temperature of 150 °C showed the greatest suitability for use in UV optoelectronic applications, as they exhibited high stability even when subjected to low applied bias voltages [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…MoO 3 thin film will be grown using the ANRIC Technologies brand (AT410) ALD system. [ 23 ] The Mo‐based organometallic precursor material bis( t ‐butylimido)bis(dimethylamino)molybdenum(VI) ((NtBu) 2 (NMe 2 ) 2 Mo) is deposited on the substrate surface in an argon atmosphere (20 sccm—99.999% purity) at low pressure (≈0.3 torrs). The open time of the valve between the growth chamber and the precursor material chamber, the temperature of the growth chamber, and the controlled heating of the precursor material chamber (≈80 °C) determine the amount of material deposited on the substrate surface.…”
Section: Methodsmentioning
confidence: 99%
“…However, recently the researchers did not detect a good photocurrent at 0 V by using MoO 3 /n-type Si. [23,24] The MoO 3 /Ir/Si PDs work by utilizing the MoO 3 layer as a hole transport layer, the Ir layer as a Schottky barrier, and the Si substrate as a charge collection layer. Light incident on the Ir metallic layer excites hot electrons, which are then transported through the Schottky barrier, leading to the formation of a photocurrent [30] this current can then be measured and used to determine the presence or absence of light.…”
Section: Electrical I-v Curvesmentioning
confidence: 99%